Promoting Therapeutic Recovery Through Biophilic Design Integration in a Leprosy Centre, Dutse, Nigeria - Abubakar, Yazid Abubakar; Isa, Abdul; Gajale, Musa Gajale (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
Humans' reliance on nature has reinforced the idea that being in a variety of healthy natural environments is essential to one's physical, psychological, and even moral well-being. This connection has shaped the decisions that people make in order to survive as a species and has led to significant changes in the natural and physical framework of the human world. In Nigeria, for example, there were over 2,000 new cases of leprosy in 2014, with an estimated 1,000 deaths from the disease. Despite this, there are only a few leprosy clinics, which are housed in various tertiary teaching hospitals across the nation. These facilities lack the necessary natural elements integrated into their design, which helps patients feel more connected to their natural surroundings. As such, this research aims to integrate biophilic design in a Leprosy Center, thereby creating a connection between life, nature and the built environment which evolves architecture that can positively contribute to the healing and psychological recovery of leprosy patients. Based on existing literature correlating biophilic design patterns and biological responses, strategies for the integration of biophilic design patterns were developed based on three broad patterns of biophilic design namely; Nature in the space, Natural analogues, and Nature of the space. ‘Nature in the space’ has seven patterns with fifteen proposed biophilic architectural strategies while ‘Natural analogues’ and ‘Nature in the space’ have three patterns with six proposed biophilic architectural strategies each. These strategies provided a design guideline for incorporating nature into a healthcare setting.